Addressing voltage hysteresis in Li-rich cathode materials via gas–solid interface modification. Issue 7 (25th January 2023) - Zhao, Qing; Zhang, Mengke; Ye, Zhengcheng; Li, Yao; Qiu, Lang; Zheng, Zhuo; Liu, Yang; Zhong, Benhe; Song, Yang; Guo, Xiaodong
Abstract : A simple and effective gas–solid interface reaction is proposed to construct oxygen vacancies and spinel phase on a surface, which improves cyclic stability and reduces voltage hysteresis. Abstract : Li-rich layered materials have attracted much attention for their large capacity (>250 mA h g −1 ) stemming from anion redox at high voltage. However, inherent problems, such as capacity decay and voltage decay/hysteresis during cycling, hinder their commercial progress. In this work, an oxygen vacancy-accompanied spinel interface layer is constructed by gas–solid reaction via NiCO3 treatment at 650 °C, which reduces the asymmetry of anion redox and improves structural stability. Therefore, a 1 mol% NiCO3 -modified sample powerfully reduces the voltage hysteresis (∼0.23 V) in the first cycle, simultaneously exhibiting an excellent discharge capacity of 275 mA h g −1 at 0.1 C with a capacity retention of 90% for 200 cycles at 1 C.